The calcium-sensing receptor modulates the prostaglandin E2 pathway in intestinal inflammation - Gushchina, Valeriya; Kupper, Nadja; Schwarzkopf, Michael; Frisch, Gitta; Piatek, Karina; Aigner, Cornelia; Michel, Alexandra; Schueffl, Hemma; Iamartino, Luca; Elajnaf, Taha; Manhardt, Teresa; Vlasaty, Andrea; et al. (Frontiers in Pharmacology, 2023)
The prostaglandin E2 (PGE2) pathway is one of the main mediators of intestinal inflammation. As activation of the calcium-sensing receptor (CaSR) induces expression of inflammatory markers in the colon, we assessed the impact of the CaSR on the PGE2 pathway regulation in colon cancer cells and the colon in vitro and in vivo. We treated CaSR-transfected HT29 and Caco-2 colon cancer cell lines with different orthosteric ligands or modulators of the CaSR and measured gene expression and PGE2 levels. In CaSR-transfected HT29CaSR-GFP and Caco-2CaSR-GFP cells, the orthosteric CaSR ligand spermine and the positive allosteric CaSR modulator NPS R-568 both induced an inflammatory state as measured by IL-8 gene expression and significantly increased the expression of the PGE2 pathway key enzymes cyclooxygenase (COX)-2 and/or prostaglandin E2 synthase 1 (PGES-1). Inhibition of the CaSR with the calcilytic NPS 2143 abolished the spermine- and NPS R-568-induced pro-inflammatory response. Interestingly, we observed cell-line specific responses as e.g. PGES-1 expression was affected only in HT29CaSR-GFP but not in Caco-2CaSR-GFP cells. Other genes involved in the PGE2 pathway (COX-1, or the PGE2 receptors) were not responsive to the treatment. None of the studied genes were affected by any CaSR agonist in GFP-only transfected HT29GFP and Caco-2GFP cells, indicating that the observed gene-inducing effects of spermine and R-568 were indeed mediated by the CaSR. In vivo, we had previously determined that treatment with the clinically approved calcimimetic cinacalcet worsened symptoms in a dextran sulfate sodium (DSS)-induced colitis mouse model. In the colons of these mice, cinacalcet significantly induced gene expression of PGES-2 and the EP3 receptor, but not COX-2; while NPS 2143 increased the expression of the PGE2-degrading enzyme 15-hydroxyprostaglandin dehydrogenase (15-PGDH). Importantly, neither treatment had any effect on the colons of non-DSS treated mice. Overall, we show that activation of the CaSR induces the PGE2 pathway, albeit with differing effects in vitro and in vivo. This may be due to the different microenvironment in vivo compared to in vitro, specifically the presence of a CaSR-responsive immune system. Since calcilytics inhibit ligand-mediated CaSR signaling, they may be considered for novel therapies against inflammatory bowel disease.